Incidence and treatment of chylothorax after cardiac surgery in children: Analysis of a large multi-institution database - Mery, Carlos M.; Moffett, Brady S.; Khan, Muhammad S.; Zhang, Wei; Guzmán-Pruneda, Francisco A.; Fraser, Charles D.; Cabrera, Antonio G. (The Journal of thoracic and cardiovascular surgery, 2014)
There is limited information regarding the true incidence of and risk factors for chylothorax after pediatric cardiac surgery. The objective of this study was to determine, from a large multi-institution database, incidence, associated factors, and treatment strategy in patients undergoing pediatric cardiac surgery. All patients younger than 18 years in the Pediatric Health Information System (PHIS) database who underwent congenital heart surgery or heart transplant from 2004 to 2011 were included. Procedure complexity was assessed by Risk Adjustment for Congenital Heart Surgery-1. In all, 77,777 patients (55% male) of median age 6.7 months were included. Overall incidence of chylothorax was 2.8% (n = 2205), significantly associated with increased procedure complexity, younger age, genetic syndromes, vein thrombosis, and higher annual hospital volume. Patients with multiple congenital procedures had the highest incidence. Incidence increased with time, from 2% in 2004 to 3.7% in 2011 (P < .0001). Chylothorax was associated with longer stay (P < .0001), increased adjusted risk for in-hospital mortality (odds ratio, 2.13; 95% confidence interval, 1.75-2.61), and higher cost (P < .0001), regardless of procedure complexity. Of all patients with chylothorax, 196 (8.9%) underwent thoracic duct ligation or pleurodesis a median of 18 days after surgery. Total parenteral nutrition, medium-chain fatty acid supplementation, and octreotide were used in 56%, 1.7%, and 16% of patients, respectively. Chylothorax is a significant problem in pediatric cardiac surgery and is associated with increased mortality, cost, and length of stay. Strategies should be developed to improve prevention and treatment.